2019
DOI: 10.1016/j.jorganchem.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrimetallic complexes of iron and ruthenium based on vinyliminium dithiocarboxylate ligands

Abstract: 2 = CO2Me) provide a versatile entry point for many subsequent transformations, such as their reaction with carbon disulfide to provide zwitterionic dithiocarboxylate products. These compounds react with the coordinativelyunsaturated ruthenium vinyl precursors [Ru(CH=CHR 3)Cl(CO)(PPh3)2] (R 3 = C6H4Me-4, 1-Pyrenyl) to yield heterotrimetallic Fe2Ru compounds, exhibiting vinyl moieties at both iron and ruthenium centres. The emission associated with the pyrenyl unit is enhanced in the diiron vinyliminium rutheni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…In particular, the sequential assembly of one isocyanide and one alkyne provides easy access to cationic complexes with a bridging vinyliminium ligand ( 1 , Figure ), , displaying a versatile chemistry . Recent studies have shown that these compounds possess a promising anticancer potential, their cytotoxic activity being attributable to a multimodal action, including ROS generation, DNA binding, and fragmentation to monoiron species …”
Section: Introductionmentioning
confidence: 99%
“…In particular, the sequential assembly of one isocyanide and one alkyne provides easy access to cationic complexes with a bridging vinyliminium ligand ( 1 , Figure ), , displaying a versatile chemistry . Recent studies have shown that these compounds possess a promising anticancer potential, their cytotoxic activity being attributable to a multimodal action, including ROS generation, DNA binding, and fragmentation to monoiron species …”
Section: Introductionmentioning
confidence: 99%
“…Some recent reports describe the utilization of a metallo-ligand approach for the synthesis of such species, in which the bimetallic system functioned as a ligand to a secondary metal. 9 On the other hand, after the isolation of the triple-decker complex [Cp 3 Ni 2 ] + , 10 followed by the first crystallographically characterized triple-decker complex, [(CpCo) 2 RC 2 B 3 H 4 ] (R = Me/H) by Grimes,11 the area of multi-decker sandwich complexes has experienced exciting developments for their potential interest as new electronic, magnetic, and/or optical materials. 12,13 These triple-decker complexes comprising a planar 11,14,15 or puckered middle ring 16,17 are remarkably resourceful which can accommodate a wide range of metals and organic substituents exhibiting substantial electron delocalization of unpaired electrons between metal centers.…”
Section: ■ Introductionmentioning
confidence: 53%
“…As a result, this ran into a practical problem to develop new synthetic strategies. Some recent reports describe the utilization of a metallo-ligand approach for the synthesis of such species, in which the bimetallic system functioned as a ligand to a secondary metal …”
Section: Introductionmentioning
confidence: 99%